The incidence of socially important diseases in convicts staying in correctional institutions of the penitentiary system in Lipetsk Region - S. V. Provotorova; N. I. Briko; A. Yu. Brazhnikov; S. D. Forostov (Туберкулез и болезни лёгких)
The high incidence of socially important infections among convicts and the specific nature of the penitentiary system require a special approach to the organization of epidemiological surveillance over such infections as HIV infection, tuberculosis and chronic parenteral viral hepatitis.The objective: to assess the significance of social infections in the incidence of convicts staying in correctional facilities of the Lipetsk regional penal system, and to determine areas for epidemiological surveillance improvement.Subjects and methods. The article presents statistical processing and analysis of data from official statistics from Medical Sanitary Unit no. 48 of the Russian Penitentiary System, collected from 2012 to 2018 reflecting the incidence in the inmates staying the Lipetsk regional penal system.Results. The analysis of data on primary incidence of socially important infections among convicts revealed the following: tuberculosis incidence among convicts who are serving sentences in the penal colonies is significantly higher compared with newly convicted inmates and those staying in prisons; the lowest incidence of chronic viral hepatitis is recorded among newly convicted inmates, and the highest among convicts serving prison sentences; the registration of cases of HIV infection among convicts revealed statistically significant differences in the incidence in convicts serving sentences in the colonies, compared with persons serving sentences in prisons.The identification of these trends allows highlighting the need to optimize epidemiological surveillance and expand the information system by adding information about the specific behavior of convicts.